Socioeconomic condition and dietary habits in relation to oral health in 12-year-old children from Sarajevo, Bosnia-Hercegovina - Zukanović, Amila; Nakaš, Enita; Marković, Nina; Arslanagić, Amra (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2018)
Introduction: Living conditions and socioeconomic status are the significant determinants of oral health. The research goal was toanalyze the dietary habits of 12-year-old children in Sarajevo, Bosnia-Hercegovina. Another goal was to investigate the differences infood cariogenicity of children living under different socioeconomic conditions and to determine their relationship with the oral health. Materials and methods: The sample included 109 children, classified in groups of high, average and low socioeconomic status. Basedon the survey and examination, data on nutrition and caries experience (DMFT index) were obtained. Results: There was a difference in dietary habits between children living under different conditions. Children of high socioeconomicstatus (SES) had a more favorable number of daily meals comparing to children of low socioeconomic status. The average DMFTindex, as a measure of caries experience of 12-year-old children amounted 4.8(±3.2). Children of high socioeconomic status hadsignificantly lower caries experience than those from average and low statuses (high SES DMFT 3,60±2,84SD vs. middle SESDMFT 5,28±3,83SD and low SES DMFT 5,47±2,53SD; p<0.05).